Penyediaan Air Bersih di Pesantren An-Nur dan Pesantren Darussalam Kecamatan Sungai Kakap Kabupaten Kubu Raya - RM Rustamaji; Kiki Prio Utomo; Hendri Sutrisno (Universitas Muhammadiyah Pontianak, 2018)
An-Nur and Darussalam Boarding School use well water for bathing, washing and latrines (MCK). However, well water contains high levels of iron and manganese. Therefore, it's needed clean water treatment technology. The water treatment system consists of aeration, adsorption, and filtration. The purpose of PKM is to provide clean water for partners. The method is a participatory and collaborative method whereby partners participate in planning, socialization and training, and operation and maintenance of water treatment plant. The PKM product is easy-to-use water treatment plant and the processed water is odorless, not turbid and colorless or clear. The main key to the success of clean water treatment PKM in An-Nur and Darussalam Boarding School is good communication and smoothly between PKM team and partners.